National Policies and Strategies - CGIAR System Organization (CGIAR System Organization, 2023)
This poster was prepared for the ‘Ethiopia CGIAR consultation workshop and launch' held last 29-30 March 2023. Showing information about NPS and it's key activities in Ethiopia.